SCUBA DIVING MODEL FOR PROFESSIONAL DEVELOPMENT SUSTAINABLE OF THAILAND - Sakkaew , Panya; Utumpa, Paveena Utumpa (Academic Journal of Thailand National Sports University, 2024)
The research objectives were: (1) to study the operating conditions and the need for scuba diving model to develop sustainable personnel standards of Thailand from executives, entrepreneurs and scuba diving instructors, totaling 27 people using in-depth interviews, the data was analyzed using content analysis, (2) to create and develop scuba diving model to develop sustainable personnel standards of Thailand, (3) to try out scuba diving model with a group of 7 experienced scuba diving students to develop sustainable personnel standards of Thailand. The quantitative research instrument was questionnaire with reliability level and data were analyzed using basic statistics, and (4) to study the interactions of scuba diving model to develop sustainable personnel standards of Thailand among 400 stakeholders using standard and indicator interaction questionnaires. Data were analyzed using five-way ANOVA and One Sample t-test. The results of the research showed that the model consisted of 4 standards and 41 indicators as follows: 1) Standards for scuba diving sports practice skills, 12 indicators, 2) Scuba diving management standards 9 indicators, 3) Scuba diving learner standards 8 indicators, 3) Scuba diving learner standards 8 indicators, 4) Scuba diving knowledge standard 12 indicators and the results of the preliminary experimental model found that the usefulness. at a high level ( = 4.14, S.D. = 0.66), followed by accuracy is at a high level ( = 4.07, S.D. = 0.71) and suitability is at a high level ( = 4.00, S.D. = 0.70). The results of the experiment with stakeholders showed that standards for the management of sample groups with different characteristics gave no different evaluation scores. And another 3 standards, practical skills, learners, and knowledge, found that the interaction of population characteristics variables affected the difference in assessment scores. Consider that scores against criteria (Mean score equal to 3.50) was found to be higher than the specified criteria with statistical significance at the .05 level.